2019
DOI: 10.1136/bmjopen-2018-025806
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns, persistence and adherence rates in patients with type 2 diabetes mellitus in Japan: a claims-based cohort study

Abstract: ObjectiveTo determine real-world trends in antidiabetic drug use, and persistence and adherence, in Japanese patients with type 2 diabetes mellitus (T2DM).DesignRetrospective evaluation of administrative claims data (2011–2015) using the Japan Medical Data Center (JMDC) and Medical Data Vision (MDV) databases.SettingAnalysis of two administrative claims databases for Japanese patients with T2DM.ParticipantsAdults (aged ≥18 years) with an International Classification of Diseases, 10th Revision code of T2DM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 39 publications
6
58
1
Order By: Relevance
“…DPP4 inhibitors have demonstrated sufficient efficacy in lowering blood glucose with a lower risk of hypoglycaemia compared with other insulin secretagogues such as sulfonylureas [15]. Owing to their well-balanced benefit to risk characteristics, DPP4 inhibitors are currently the most commonly prescribed oral hypoglycaemic agents in Japan [16].…”
Section: Introductionmentioning
confidence: 99%
“…DPP4 inhibitors have demonstrated sufficient efficacy in lowering blood glucose with a lower risk of hypoglycaemia compared with other insulin secretagogues such as sulfonylureas [15]. Owing to their well-balanced benefit to risk characteristics, DPP4 inhibitors are currently the most commonly prescribed oral hypoglycaemic agents in Japan [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with a PDC 0.8 have been considered to have good adherence to treatment 27,29 , this cut-off should be interpreted with caution. Adherence rate was defined as PDC divided by the number of days.…”
Section: Classification Of Dpp-4i Administration Frequencies and Defimentioning
confidence: 99%
“…A recently published real-world study, based on Japanese health insurance claims data, found that the use of, and persistence and adherence to, DPP-4i-containing regimens was high among previously treated and previously untreated Japanese patients with T2DM 27 . The availability of new treatment regimens in Japan, particularly once-weekly dosing, coupled with universal health insurance coverage and unrestricted access to almost any healthcare provider means that patients are able to select physicians or medical facilities of their choice.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent analysis of two Japanese clinical databases (Japan Medical Data Centre [JMDC] database and Medical Data Vision [MDV] database) showed that DPP-4 inhibitors were frequently prescribed in previously untreated patients (JMDC: 44.0%; MDV: 54.8%) and as part of combination therapy in previously treated patients (JMDC: 74.6%; MDV: 81.1%). 23 Adherence and persistence to DPP-4 inhibitors were also found to be high in both databases. Although prior studies have indirectly compared the effects of SGLT2 inhibitors and DPP-4 inhibitors on glycaemic control, body weight and cardiovascular events, 24,25 none, to our knowledge, has compared their effects on renal function.…”
mentioning
confidence: 91%
“…For this purpose, we analysed a large Japanese medical database using patients treated with dipeptidyl peptidase‐4 (DPP‐4) inhibitors as a reference group because these drugs have been available in Japan for ~8 years, have a complementary mechanism of action to SGLT2 inhibitors and, in our experience, are widely prescribed to patients with type 2 diabetes in Japan. Indeed, a recent analysis of two Japanese clinical databases (Japan Medical Data Centre [JMDC] database and Medical Data Vision [MDV] database) showed that DPP‐4 inhibitors were frequently prescribed in previously untreated patients (JMDC: 44.0%; MDV: 54.8%) and as part of combination therapy in previously treated patients (JMDC: 74.6%; MDV: 81.1%) . Adherence and persistence to DPP‐4 inhibitors were also found to be high in both databases.…”
Section: Introductionmentioning
confidence: 99%